ANALISIS TINGKAT PERPUTARAN PIUTANG PADA PT. ANUGRAH TEXTILE DI JAKARTA - Featy Octaviany; Kustari Kustari; Nofi Anasari (JURNAL LENTERA AKUNTANSI, 2020)
In achieving profit at PT. Anugrah Textile is needed analysis of the level of accounts receivable turnover to minimize high receivables. The way to analyze the level of accounts receivable turnover can be done through accounts receivable turnover, collection of receivables, arrears of receivables and collection of receivables. The problem discussed in this study is how the level of accounts receivable turnover at PT. Anugrah Textile Jakarta? Based on these problems, this study aims to determine the level of accounts receivable turnover at PT. Anugrah Textile Jakarta. The research method in this research is a quantitative descriptive analysis method used for testing receivables namely accounts receivable turnover, collection of receivables, arrears of receivables and collection of receivables. The population of this research is all sales and receivables report data. The sampling method is a saturated sampling technique, where all population data are used as samples (population research). So the sample is determined by a whole number of data. To get comprehensive data, accounts receivable data is used as a primary data source. The results of observations and interviews as a secondary data source. The results showed that the level of accounts receivable turnover at PT. Anugrah Textile Jakarta for 3 years has decreased.Keyword: Turnover, receivable, analysis